The Physical Property Values and Suitability of Coarse Aggregates from Various Sources Used in Selected Building Construction Projects in the Kathmandu Valley - Bhatta, Anil; Shrestha, Jagadiswar Man (Journal of Advanced Research in Geo Sciences & Remote Sensing; Vol 9 No 3&4 (2022): Journal of Advanced Research in Geo Sciences & Remote Sensing, 2023)
To examine the values of physical properties and suggest suitability of Coarse Aggregates from different Sources used in Selected Building Construction Projects within Kathmandu Valley. Construction of Journalism and Mass Communication Administrative Building, Construction of Central Department of Management Academic Building, Construction of Office of Registrar Building of Tribhuvan University along with Paropakar Woman and Fertility Hospital Service Extension and Research Building have been considered for study. Gradation/Sieve Analysis, Crushing Test, Abrasion Test, Impact Test on Aggregates, Shape Test Specific Gravity and Water Absorption Test and Soundness Test were done at lab. The data collected from both primary and secondary sources were summarized, classified, tabulated, categorized. For the quantitative data like various tests of coarse aggregates from different sources were tabulated, processed and a comparison was made between different physical parameters and values to standard guidelines of IS, DUDBC, NS and NS. The gradation analysis of coarse aggregates from both source lies within the limit values but the coefficient of uniformity were beyond the limit and coarse aggregates from both sources were found to be poorly graded. The LAAV parameter has no significance role in building construction related issues. The Strength, Specific Gravity, Soundness, ACV, AIV for coarse aggregates from source 2 resembles better physical properties than coarse aggregates from source 1. But, the textural parameters like FI and EI of coarse aggregates from source 1 resembles better properties than source 1but does not lie within permissible limits. This was mainly because of using cone and impact crusher for source-1 and only cone and impact crusher 2. How to cite this article: Bhatta A, Shrestha JM. The Values of Physical Properties and Suggest Suitability of Coarse Aggregates from Different Sources used in Selected Building Construction Projects within Kathmandu Valley. J Adv Res Geo Sci Rem Sens 2022; 9(3&4): 26-41. DOI: https://doi.org/10.24321/2455.3190.202202